2016
DOI: 10.9775/kvfd.2016.15832
|View full text |Cite
|
Sign up to set email alerts
|

Sığırlarda GSBL ve AmpC Sentezleyen Escherichia coli’nin Prevalansı ve Karakterizasyonu

Abstract: Citation of This ArticleAslantaş Ö, Elmacıoğlu S, Yılmaz EŞ: Prevalence and characterization of ESBL-and AmpC-producing Escherichia coli from cattle. Kafkas Univ Vet Fak Derg, 23, 63-67, 2017. DOI: 10.9775/kvfd.2016 AbstractIn this study, it was aimed to determine the prevalence of extended spectrum β-lactamase (ESBL) and/or AmpC type β-lactamase (AmpC) producing Escherichia coli from cattle in Hatay. For this purpose, 312 rectal swabs samples were collected from apparently healthy cattle. ESBL production was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…The real prevalence of pAmpC beta-lactamase producing E. coli is still unknown in healthy cattle and sheep in Turkey. There is only one local study conducted on this topic in healthy cattle in Turkey and it was found only one E. coli isolate carrying ampC (cmy) gene out of 312 cattle rectal swab samples [17] . On the other hand, there is no report for pAmpC beta-lactamase producing E. coli in healthy sheep in Turkey.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The real prevalence of pAmpC beta-lactamase producing E. coli is still unknown in healthy cattle and sheep in Turkey. There is only one local study conducted on this topic in healthy cattle in Turkey and it was found only one E. coli isolate carrying ampC (cmy) gene out of 312 cattle rectal swab samples [17] . On the other hand, there is no report for pAmpC beta-lactamase producing E. coli in healthy sheep in Turkey.…”
Section: Discussionmentioning
confidence: 99%
“…Approximate sample size of the study was determined to be 138 using a 10% expected field prevalence [16,17] at the 95% confidence level and the desired absolute precision of 5% [20] , but more animals were included to the present study for higher precise results. Twenty dairy cattle and 12 sheep farms with no close contact to cattle farms were selected randomly from different locations of Burdur.…”
Section: Samplingmentioning
confidence: 99%
See 1 more Smart Citation
“…Escherichia coli is the most common type of abundant bacteria in human and animal intestines. Some serotypes are pathogenic and can cause diarrhea, meningitis, urinary tract infections, sepsis, or pneumonia in humans and animals [7,8] . Due to the extensive use of antibiotics in veterinary clinics, it is easy for E. coli to evolve resistance to drugs and become a reservoir for antibiotic resistance and resistance genes [9,10] .…”
Section: Introductionmentioning
confidence: 99%